Synthesis and spectroscopic characterization of organotin(IV) complexes with 2-benzoylpyridine-N(4)-cyclohexylthiosemicarbazone (HBPCT): X-ray crystal structure of [PhSnCl2(BPCT)] - Md. Abu, Affan; M.A., Salam; Fasihuddin B., Ahmad; Ismail, Jusoh; Mustaffa B., Shamsuddin; Hapipah M., Ali (Elsevier, 2011)
The reaction of 2-benzoylpyridine-N(4) cyclohexylthiosemicarbazone [HBPCT, (1)] ligand with organotin(IV) chloride(s) lead to the formation of three new organotin(IV) complexes: [MeSnCl2(BPCT)] (2), [PhSnCl2(BPCT)] (3) and [Ph2SnCl(BPCT)] (4). The ligand (1) and its organotin(IV) complexes (2–4) have been synthesized and characterized by CHN analyses, molar conductivity, UV–Vis, FT-IR and 1 H NMR spectral studies. The single crystal X-ray diffraction studies indicated that [PhSnCl2(BPCT)] (3) is six coordinated and adopts strongly a distorted octahedral configuration with the coordination through pyridine-N, azomethine-N and thiolato-S atoms of the ligand. The crystal system of [PhSnCl2(BPCT)] (3) is orthorhombic with space group P2ac2n and the unit cell dimensions: a = 28.1363(5) Å, b = 9.5970(2) Å,c = 9.4353(2) Å.